Spatial and Temporal Variability and Long-Term Trends in Skew Surges Globally - Mawdsley, Robert J.; Haigh, Ivan D. (Frontiers in Marine Science, 2016)
Storm surges and the resulting extreme high sea levels are among the most dangerous natural disasters and are responsible for widespread social, economic and environmental consequences. Using a set of 220 tide gauges, this paper investigates the temporal variations in storm surges around the world and the spatial coherence of its variability. We compare results derived from two parameters used to represent storm surge: skew surge and the more traditional, non-tidal residual. We determine the extent of tide-surge interaction, at each study site, and find statistically significant (95% confidence) levels of tide-surge interaction at 59% of sites based on tidal level and 81% of sites based on tidal-phase. The tide-surge interaction was strongest in regions of shallow bathymetry such as the North Sea, north Australia and the Malay Peninsula. At most sites the trends in the skew surge time series were similar to those of non-tidal residuals, but where there were large differences in trends, the sites tended to have a large tidal range. Only 13% of sites had a statistically significant trend in skew surge, and of these approximately equal numbers were positive and negative. However, for trends in the non-tidal residual there are significantly more negative trends. We identified 8 regions where there were strong positive correlations in skew surge variability between sites, which meant that a regional index could be created to represent these groups of sites. Despite, strong correlations between some regional skew surge indices, none are significant at the 95% level, however, at the 80% level there was significant positive correlation between the north-west Atlantic - south and the North Sea. Correlations between the regional skew surge indices and climate indices only became significant at the 80% level, where Nińo 4 was positively correlated with the Gulf of Mexico skew surge index and negatively correlated with the east Australia skew surge index. The inclusion of auto-correlation in the calculation of correlation greatly reduced their significance, especially in the short time-series used for the regional skew surge indices.